APLIKASI PENCARIAN LOKASI PERGURUAN TINGGI DENGAN OBJEK MENGGUNAKAN METODE VIRTUAL REALITY PADA KOTA MAKASSAR - Usman Usman (Journal of Innovation Research and Knowledge, 2023)
The development of information technology is very rapid, along with the need for information and the growth of human intelligence. Today, there are many information systems used to support and solve problems that usually arise within an organization, company, or government agency. Information systems are expected to improve the performance of an organization or agency by making it more effective, efficient, and easy to receive the information to be transmitted. Geographic Information System (GIS) is a technology that becomes an auxiliary and very essential tool, as well as the field of science that uses Virtual Reality (VR), which is the technology that displays images or objects surrounding them in 360 degrees. Makassar is famous for its district residents, who come from every district. A lot of high slopes are scattered in Makassar, but not everyone knows about the college in Makassar, especially about the shape or picture of the campus. To make it easier to inform people and students wherever they are who are in need of information about the University of London and its descriptions, the geographical information system of web-based university location search is perfect to meet these needs.